2019
DOI: 10.32674/jis.v9i2.677
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Learning in Transnational Articulation Programs

Abstract: Many Chinese universities engage in transnational higher education by establishing articulation programs with international partners. Although research has broadly investigated transnational higher education topics, few studies have explored Chinese students’ intercultural learning and adjustment experiences in these programs. This qualitative study explored seven Chinese students’ experiences in two China-Australia articulation programs to add insights to this under-researched topic. The findings indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In terms of the main findings of the reviewed studies, only two of them (Santos et al 2014;O'Brien et al 2019) report an increase of culture-specific knowledge among their main outcomes. Most studies focus on the experiential aspects of intercultural learning, mentioning the value of: 'embodied' experiences (Donelan 2010;Tonkin and Coudray 2016;Frimberger 2016), 'immersion', 'boundary' and'belonging' experiences (Hepple et al 2017;Mesker et al 2018;Dai and Garcia 2019), or even the concrete experience of the 'stigmatised position of the other' (Børhaug and Weyringer 2019). Other experiential and affective aspects were also highlighted: cultural/cognitive dissonance (Allan 2003;Mitchell and Paras 2018), non-essentialist engagement (Holmes et al 2015), enacted understanding of the Other (Gill 2007), and mutual enrichment (Bedeković 2017).…”
Section: Main Methods Used Findings and Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the main findings of the reviewed studies, only two of them (Santos et al 2014;O'Brien et al 2019) report an increase of culture-specific knowledge among their main outcomes. Most studies focus on the experiential aspects of intercultural learning, mentioning the value of: 'embodied' experiences (Donelan 2010;Tonkin and Coudray 2016;Frimberger 2016), 'immersion', 'boundary' and'belonging' experiences (Hepple et al 2017;Mesker et al 2018;Dai and Garcia 2019), or even the concrete experience of the 'stigmatised position of the other' (Børhaug and Weyringer 2019). Other experiential and affective aspects were also highlighted: cultural/cognitive dissonance (Allan 2003;Mitchell and Paras 2018), non-essentialist engagement (Holmes et al 2015), enacted understanding of the Other (Gill 2007), and mutual enrichment (Bedeković 2017).…”
Section: Main Methods Used Findings and Considerationsmentioning
confidence: 99%
“…Other studies highlight limitations in the use of the concept 'culture' to refer only to a national identity, and its consequences on students' intercultural learning outcomes (Bozdag 2018;Hessel 2019). Studies also highlight the teachers' role within intercultural education initiatives, notably the need for educational support for cross-system transitions (Dai and Garcia 2019) and the importance of teacher education (Senyshyn 2018). Cloonan et al (2017) further argue that teachers' exposure to intercultural learning techniques does not guarantee an increase in their capacity to deal with interculturality in their classrooms.…”
Section: Main Methods Used Findings and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors thus called for more empirical studies on learning experiences. The argument was reinforced by Dai et al (2018) and Dai and Garcia (2019), who also discover that studies exploring Chinese students' learning experience in CFCRS programs are limited.…”
Section: Chinese Students' Learning In Transnational Programsmentioning
confidence: 99%
“…The learning experience in Chinese universities might not be helpful for students to learn in other culturally different universities (Quan et al, 2013). It is worth noting that Dai and his colleagues published a number of articles to uncover Chinese students' learning-related issues such as intercultural learning and adjustment experiences (Dai & Garcia, 2019), assessment and learning experiences , narrative approach-based self-learning experience reflection (Dai, 2018), field, habitus, and learning . These studies demonstrated Chinese students' complex intercultural learning experiences, which resulted in changes in many aspects and form a "sense of in-betweenness.…”
Section: Chinese Students' Learning In Transnational Programsmentioning
confidence: 99%